2017
DOI: 10.1101/115881
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morphological Alternations of Intraepithelial and Stromal Telocytes in Response to Salinity Challenges

Abstract: Summary statementThe article represent an experimental study in which we investigated the effect of the ssalinty on the communicating cells (telocytes) and their target cells including chloride, stem, Rodlet cells, myoblastsAbstractTelocyte is a communicating cell established relations to various types of cells. Few experimental studies are performed on telocytes. The current study investigated responce of telocytes to salinity stress in relations to osmoregualtory, immune and stem cells. We exposed Common car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…To date, telocytes have been described in all classes of vertebrates, but also in many other animal species from different taxa. For instance, Soliman and Emeish studied the distribution of telocytes in the gills of carp species Cyprinus carpio in connection to the levels of water salinity (Soliman and Emeish 2017). Ghose et al (2008) discovered telocytes in the postcaval vein of the frog Rana tigrina and demonstrated that telocytes are responsible for the rhythmic contraction of this vein, independent of the electrical conduction system of the heart.…”
Section: Question 4 Are Telocytes Described Exclusively In Humans?mentioning
confidence: 99%
“…To date, telocytes have been described in all classes of vertebrates, but also in many other animal species from different taxa. For instance, Soliman and Emeish studied the distribution of telocytes in the gills of carp species Cyprinus carpio in connection to the levels of water salinity (Soliman and Emeish 2017). Ghose et al (2008) discovered telocytes in the postcaval vein of the frog Rana tigrina and demonstrated that telocytes are responsible for the rhythmic contraction of this vein, independent of the electrical conduction system of the heart.…”
Section: Question 4 Are Telocytes Described Exclusively In Humans?mentioning
confidence: 99%
“…The PhotoFiltre software (version 6.3.2; PhotoFiltre) was used to digitally color the SEM images to make it easier to identify the detailed structures of various tissues and organs on the same electron image (Abd‐Elhafeez & Soliman, 2016; Abd‐Elhafeez & Soliman, 2017; Abdel‐latief Soliman & Ali Emeish, 2017; Abdel‐Maksoud, Abd‐Elhafeez, & Soliman, 2019; Anwar, Abd‐Elhafeez, Abdel‐maksoud, & Abdalla, 2021; Soha Soliman, Hanan Hassan, & Enas, 2017; Soliman, 2021; Soliman & Abd‐Elhafeez, 2016; Soliman, Abd‐Elhafeez, Sa, & Hh, 2016; Soliman & Madkour, 2017; Soliman & Madkour, 2021) have used these techniques.…”
Section: Methodsmentioning
confidence: 99%
“…The samples underwent postfixation by osmium tetroxide, dehydration, impregnation in a mixture of alcohol/resin and pure resin, resin embedding, and crystallization in an oven at 60 °C. Semithin sections were taken at 1 μm using an ultramicrotome Ultracut E (Reichert-Leica, Germany) and stained with toluidine blue 20,21 and Periodic acid-Schiff (PAS) 22 . Staining of semithin sections was performed after dissolving the resin using a saturated alcoholic solution of sodium hydroxide.…”
Section: Alcohol70%i 2 H 2 Hmentioning
confidence: 99%